KOLABORASI MAHASISWA DAN KARANG TARUNA MELALUI PROGRAM GEROBAK BACA SEBAGAI UPAYA MENINGKATKAN MINAT BACA ANAK - Putri, Ranti Gatrizka; Wahyuni, Dewi; Nasution, Umar Hamdan (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
The background of this activity is the lack of reading books for children in Nelayan Indah Village and the inaccessibility of reading activities throughout the community in Nelayan Indah Village. The Read Cart program aims to facilitate reading activities to increase children's reading interest in Nelayan Indah Village by bringing useful reading books to various areas in Nelayan Indah Village.               The cart program is carried out with students in collaboration with the Youth Organization in Nelayan Indah Village with the target audience being children in Nelayan Indah Village. The method of implementation in this program starts with the initial survey and identification of problems in Nelayan Indah Village, then needs analysis and solutions are carried out to the existing conditions, then the program is compiled and implemented, namely (1) Socialization of the Making of Reading Carts and Social Media Accounts for Reading Carts; (2) Designing Carts by Youth and Student Organizations; (3) Making a reading cart which is carried out offline; (4) Socialization of the Making of Carts Read Social Media Accounts; (5) Reading Cart Activities in the Field and Procurement of Competitions, as well as evaluation.               The results achieved were the creation of 2 reading carts with the same model and variation, there were more than 300 reading books consisting of fairy tale books, novels, story books, and general knowledge books, the creation of reading cart social media accounts, there were a module on how to create a social media account for Karang Taruna, and the implementation of competitions for children in Kelurahan Nelayan Indah.